Relationship between team method implementation and nurse performance - Pratiwi, Alifka; Supratman, Supratman (Jurnal EduHealth, 2024)
Introduction: Nurse performance is an activity taken by a nurse in a company in accordance with their authority and responsibilities, and high performance can bring satisfaction to service users while also improving the quality of nursing services. To improve and achieve the standard of nursing services, hospitals must adopt a nursing care system process in the ward based on the Nursing Professional Practice Model (MPKP). The team approach is a nursing care delivery strategy in which an experienced nurse leads a group of nursing personnel to provide nursing treatment to a group of customers through collaborative and collaborative efforts. Method: This is a quantitative study conducted utilizing a design for descriptive correlational research with a sample size of 97 nurses. In this study, data is collected utilizing a questionnaire. Result: Frequency Distribution Based on the application of the team method, it was discovered that the majority of the nurses were in the application of the team method below the optimal level as many as 54 people (55.7%), and the frequency distribution based on nurse performance revealed that the majority of the nurses were in lacking nurse performance as many as 65 people (67%). The Chi-squared statistical analysis resulted in a value of ρ = 0.001. This signifies that the ρ value is lower than α (ρ = 0.001 < α = 0.05). Conclusion: There is a link between using the team technique and how well nurses perform at Dr. Moewardi Regional General Hospital.